DdRAD sequencing-based genotyping for population structure analysis in cultivated tomato provides new insights into the genomic diversity of Mediterranean 'da serbo' type long shelf-life germplasm. (1st September 2020) - Esposito, Salvatore; Cardi, Teodoro; Campanelli, Gabriele; Sestili, Sara; Díez, María José; Soler, Salvador; Prohens, Jaime; Tripodi, Pasquale
Abstract: Double digest restriction-site associated sequencing (ddRAD-seq) is a flexible and cost-effective strategy for providing in-depth insights into the genetic architecture of germplasm collections. Using this methodology, we investigated the genomic diversity of a panel of 288 diverse tomato ( Solanum lycopersicum L.) accessions enriched in 'da serbo' (called 'de penjar' in Spain) long shelf life (LSL) materials (152 accessions) mostly originating from Italy and Spain. The rest of the materials originate from different countries and include landraces for fresh consumption, elite cultivars, heirlooms, and breeding lines. Apart from their LSL trait, 'da serbo' landraces are of remarkable interest for their resilience. We identified 32, 799 high-quality SNPs, which were used for model ancestry population structure and non-parametric hierarchical clustering. Six genetic subgroups were revealed, clearly separating most 'da serbo' landraces, but also the Spanish germplasm, suggesting a subdivision of the population based on type and geographical provenance. Linkage disequilibrium (LD) in the collection decayed very rapidly within <5 kb. We then investigated SNPs showing contrasted minor frequency allele (MAF) in 'da serbo' materials, resulting in the identification of high frequencies in this germplasm of several mutations in genes related to stress tolerance and fruit maturation such as CTR1 and JAR1 . Finally, a mini-core collection of 58 accessions encompassing most of the diversity was selected for further exploitation of key traits. Our findings suggest the presence of a genetic footprint of the 'da serbo' germplasm selected in the Mediterranean basin. Moreover, we provide novel insights on LSL 'da serbo' germplasm as a promising source of alleles for tolerance to stresses.